Earthquake design and assessment of masonry structures: review and applications - Lourenço, Paulo B. (2009)
The seismic response of buildings is particularly difficult to characterize. This paper provides a review on the seismic analysis of masonry structures, incorporating or not box-behaviour. The possibilities are discussed and selected results are presented. The knowledge seems to be consolidated in case of box behaviour, but considerable efforts are still needed when box behaviour is not present. In this case, several comparisons are provided between push-over methods and time integration dynamic analysis.